The use of high-frequency skin ultrasound in the diagnosis of lipodermatosclerosis - Woźniak Witold; Danowska Anna; Mlosek Robert K. (Journal of Ultrasonography, 2020)
Introduction: Lipodermatosclerosis is a symptom of severe venous insufficiency, the diagnosis of which is based on the clinical picture. Although the histopathology of the skin and the subcutaneous tissue allows for the most reliable diagnosis, it is not recommended due to healing disorders. Aim: The aim of this study was to assess the usefulness of high-frequency ultrasound in the diagnosis of lipodermatosclerosis. Materials and methods: The study included 10 patients with lipodermatosclerosis who underwent Duplex Doppler ultrasound of lower limb veins, high-frequency ultrasound of the tibial skin, and radiography of the lower leg, all of which were analyzed in correlation with clinical symptoms. Results: The study group included 9 women and 1 man aged 39–81 years. Manifestations of lipodermatosclerosis were detected in 14 limbs. High-frequency ultrasound showed that the mean dermis thickness at the affected sites was 2.63 mm, and was significantly thicker compared to healthy skin (1.45 mm) (p = 0.00002). Higher echogenicity was detected in the affected body regions in 85.7% of cases for the skin and 92.9% of cases for the subcutaneous tissue. Subcutaneous and vascular wall calcifications were detected in 92.9% and 78.6% of cases, respectively. Fibrosis was observed in all limbs, and compression sonoelastography showed that the compliance of the subcutaneous tissue was lower than that of muscles. The border between the skin and the subcutaneous tissue was blurred in 57.1% of cases. Radiography revealed thickening of the affected skin regions in all limbs, with calcifications detected in 85.7% of cases. A blurred border between the skin and the subcutaneous tissue was observed in 35.7% of limbs. Conclusion: High-frequency ultrasonography of the skin and the subcutaneous tissue in the lower legs supported with radiological findings is highly useful in the diagnosis of lipodermatosclerosis.